Effects of sewage sludge and livestock manure vermicompost on growth and yield of maize (Zea mays L.) - Salleh, Mohd Syahmi (2015)
Sewage sludge and livestock manure are being produced in great quantity on a daily basis. Improper disposal of these wastes would cause adverse effects on the environment and human health. Vermitechnology can be used to manage and recycle these wastes to organic fertilizers for crop production. The objectives of this study were to: 1) determine the potential of earthworm to convert sewage sludge into vermicompost, 2) compare the chemical properties of sewage sludge vermicompost with livestock manure vermicompost, 3) determine the effects of sewage sludge and livestock manure vermicompost on yield, biomass and nutrient uptake of maize (Zea mays), 4) determine the effects of sewage sludge and livestock manure vermicompost on heavy metal accumulation in the soil and plant, and 5) assess economic potential of substituting mineral fertilizer with vermicompost in maize cultivation. Sewage sludge (SS), cattle manure (CM) and goat manure (GM) were subjected to pre-composting for 15 days prior to vermicomposting for another 30 days. Earthworm number and biomass were recorded before and after vermicomposting. Vermicompost produced was evaluated as a fertilizer for maize (Zea mays) cultivation. The experimental design was a randomized complete block design (RCBD) with three replications (blocks). Treatments involved mixture of vermicompost (VC) and mineral fertilizer (MF) in the following ratios of VC and MF: 100% VC (T1 for SS VC, T5 for CM VC and T9 for GM VC), 75:25 (T2 for SS VC, T6 for CM VC and T10 for GM VC), 50:50 (T3 for SS VC, T7 for CM VC and T11 for GM VC), 25:75 (T4 for SS VC, T8 for CM VC and T12 for GM VC), and 100% MF (T13) along with T14 (without fertilizer) as control. Standard laboratory procedures were used to determine chemical properties of vermicompost and soil. Nutrient uptake (N, P, and K) and heavy metals (Pb, Cd, Cu and Zn) content in the plant tissues were also measured. Data collected were statistically analysed using analysis of variance (ANOVA) followed by Duncan‟s new multiple range test (DNMRT) for mean comparison. Earthworm growth performance was significantly low in the sewage sludge compared to the livestock manure due to the high amounts of NH4 (1736.07 ppm), low pH (5.22) and low C/N ratio (6.64) at the beginning of vermicomposting process. Sewage sludge vermicompost contained significantly higher amount of total N, exchangeable NH4, total and available P and exchangeable Ca compared to livestock manure vermicompost. Vermicompost produced in this study was considered safe to be used in maize cultivation due to the lower heavy metal content than the maximum permissible limits. The fresh yield of maize from sewage sludge vermicompost based treatments was not significantly different compared to the livestock manure vermicompost based treatments. Combined application of 25% and 50% vermicompost with mineral fertilizer (T3, T4, T7, T8 and T12) produced no significant difference in fresh yield and plant biomass as compared to 100% mineral fertilizer (T13). Nitrogen uptake in these treatments was also not significantly different. Significant increase of Pb (28.57 mg kg-1) and Cd (1.03 mg kg-1) in the soil at harvest were recorded in T13. However, heavy metal content in the soil and plant tissues for all treatments did not exceed the standard permissible limits. Substitution of 50% mineral fertilizer with vermicompost was economically viable due to the increase in total net benefit at 4.87% (RM162.52) and the benefit-cost ratio from 2.70 to 2.83 as compared to the 100% mineral fertilizer application. This study has highlighted the potential of sewage sludge and livestock manure vermicompost to substitute mineral fertilizers in maize cultivation through vermitechnology and biological agriculture concept. However,study on the pathogenic aspect of sewage sludge and livestock manure vermicompost is necessary to evaluate the possibility of disease incidence.